Borrelia burgdorferi-Induced Changes in the Class II Self-Immunopeptidome Displayed on HLA-DR Molecules Expressed by Dendritic Cells - Gutierrez-Hoffmann, Maria G.; O'Meally, Robert N.; Cole, Robert N.; Tiniakou, Eleni; Darrah, Erika; Soloski, Mark J. (Frontiers in Medicine, 2020)
The MHC class II antigen processing and presentation pathway has evolved to derive short amino acid peptides from proteins that enter the endocytic pathway, load them onto MHC class II molecules and display them on the surface of antigen presenting cells for recognition by CD4+ T cells. Under normal circumstances, peptides bound to MHC class II molecules are derived from host (self) proteins and not recognized by T cells due to tolerance mechanisms. Pathogens induce significant changes in the biology of antigen presenting cells, including upregulation of MHC processing and presentation. We therefore hypothesized that exposure to pathogens may alter the repertoire of self-peptides bound to MHC class II molecules. To test this hypothesis, we isolated monocyte-derived dendritic cells from healthy subjects, exposed them to the TLR-2 agonist lipoteichoic acid or live Borrelia burgdorferi, the causative agent of Lyme disease, and isolated and characterized HLA-DR associated peptides using mass spectroscopy. Our results show that lipoteichoic acid-stimulated, B. burgdorferi-stimulated and unstimulated monocyte-derived dendritic cells largely derive their self-peptides from similar overlapping sets of host proteins. However, lipoteichoic acid and B. burgdorferi stimulation promote the processing and presentation of new sets of HLA-DR associated self-peptides derived from unique protein sources. Examination of processes and compartments these proteins reside in, indicate that activation of monocyte-derived dendritic cells changes the range of host self-proteins available for processing and presentation on MHC class II molecules. These findings reveal that the HLA-DR-bound self-immunopeptidome presented by mo-DCs is dynamic in nature and changes with activation state reflective of cellular function. In addition, among the repertoire of self-peptides bound to HLA-DR are several epitopes known to be recognized by autoreactive T cells. differential functional capabilities. These studies are relevant to our basic understanding of pathogen-induced changes in monocyte-derived dendritic cell function, and the mechanisms involved in infection-induced autoimmune illnesses such as Lyme arthritis.